Software packages for library automation - Vasanth N; Mudho, Mahesh V (New Delhi Ess Ess, 2000)
The book Software packages for Library Automation is first of its kind in the field of Library and Information Science. Different Software packages have been analysed in a systematic way and the book provides exhaustive bibliography. This book points out
Keywords: Libraries-Automation; Integrated library systems (Computer systems)